H2S Detection by Vertically Aligned CuO Nanowire Array Sensors - Chen, Jiajun; Wang, Kai; Hartman, Lisa; Zhou, Weilie (Journal of physical chemistry. C, 2008)
Chemical sensors based on vertically aligned p-type CuO nanowire arrays have been fabricated by in situ micromanipulation in a scanning electron microscope. The sensors are capable of detecting air-diluted H2S to the parts per billion level. Different mechanisms have been proposed for the detections of low and high concentrated H2S. The recoverable detection for low concentrations can be explained by an oxygen adatom related process, while an interface reaction model fits for the high concentration detection, which also explains the exponential sensing response. Furthermore, selective detection for H2S has also been investigated. The sensor demonstrated strong selectivity for H2S, as compared with the responses to high concentrations of H2, CO, and NH3.